2000
DOI: 10.1021/jm990461z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ligands Lacking a Positive Charge for the δ- and μ-Opioid Receptors

Abstract: Recently we reported using minilibraries to replace Lys(9) [somatostatin (SRIF) numbering] of the potent somatostatin agonist L-363,301 (c[-Pro-Phe-D-Trp-Lys-Thr-Phe-]) to generate the potent neurokinin receptor (NK-1) antagonist c[-Pro-Phe-D-Trp-p-F-Phe-Thr-Phe-]. This novel cyclic hexapeptide did not bind the SRIF receptor. Thus, a single mutation converted L-363,301, a SRIF agonist with potency ca. 2-8 times the potency of SRIF in laboratory animals,(24) into a selective NK-1 receptor antagonist with an IC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…In most cases, the removal or derivatization of this group resulted in inactive derivatives or antagonists; some outstanding examples of antagonists are given: the cyclic β-casomorphin-derived opioid peptide CHO-Dmt-c[D-Orn-2-Nal-Pro-Gly] showed MOR and DOR antagonist activity [100]; the cyclic opioid peptides containing 3-(2,6-dimethyl-4-hydroxyphenyl)propanoic acid (Dhp), (2S)-2-methyl-3-(2,6-dimethyl-4-hydroxyphenyl)-propanoic acid [(2S)-Mdp], or (3S)-3-methyl-3-(2,6-dimethyl-4-hydroxyphenyl) propanoic acid [(3S)-Mdp] instead of the classic Tyr1 residue, resulted in opioid antagonists [101][102][103]; the MOR and KOR antagonist N-formylnormorphine [104]; the dynorphin A analogue cyclo(N,5)[Trp3,Trp4,Glu5] dynorphin A-(1-11)NH 2 , an Nterminal to-side chain cyclic peptide showed good KOR antagonism [105].…”
Section: The Docking Of Ligands Lacking Of the Cationic Amino Groupmentioning
confidence: 99%
“…In most cases, the removal or derivatization of this group resulted in inactive derivatives or antagonists; some outstanding examples of antagonists are given: the cyclic β-casomorphin-derived opioid peptide CHO-Dmt-c[D-Orn-2-Nal-Pro-Gly] showed MOR and DOR antagonist activity [100]; the cyclic opioid peptides containing 3-(2,6-dimethyl-4-hydroxyphenyl)propanoic acid (Dhp), (2S)-2-methyl-3-(2,6-dimethyl-4-hydroxyphenyl)-propanoic acid [(2S)-Mdp], or (3S)-3-methyl-3-(2,6-dimethyl-4-hydroxyphenyl) propanoic acid [(3S)-Mdp] instead of the classic Tyr1 residue, resulted in opioid antagonists [101][102][103]; the MOR and KOR antagonist N-formylnormorphine [104]; the dynorphin A analogue cyclo(N,5)[Trp3,Trp4,Glu5] dynorphin A-(1-11)NH 2 , an Nterminal to-side chain cyclic peptide showed good KOR antagonism [105].…”
Section: The Docking Of Ligands Lacking Of the Cationic Amino Groupmentioning
confidence: 99%
“…However, it has been demonstrated that cyclic analogues of β-casomorphin, (CHO-Dmt-c 2,5 [DOrn-2-Nal-DPro-Gly] and Dhp-c 2,5 [DOrn-2-Nal-DPro-Gly]), lack the protonated nitrogen atom, and yet exhibit opioid activities as DOR ( K e = 16 and 120 nM, respectively, in the MVD) and MOR ( K e = 220 and 240 nM, respectively, in the GPI) antagonists, but did not interact with the KOR [46]. The Dhp-derivatives were the first neutral compounds not to possess the positively charged nitrogen atom for the opioid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous observations, joint D ‐Pro 2 substitution with other residues at positions 1 or 4 appeared to be better tolerated and provided ligands with biological activities similar to those of the EMs. The results on some dynorphin A analogues,128 and the assumption that certain opioid analogues lacking a cationizable N‐terminal amino group sustain receptor affinity,100, 129 led Cardillo et al. to synthesize a series of cyclic EM analogues containing D or L residues, and a Gly bridge connecting residues 1 and 4 by an amide bond 130.…”
Section: Pharmacology and Functionality Of Emsmentioning
confidence: 99%